2000
DOI: 10.1098/rspb.2000.1289
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, ticks and travels: a test of the immunocompetence-handicap hypothesis in free-ranging male sand lizards

Abstract: The immunocompetence^handicap hypothesis suggests that androgen-dependent male characters constitute honest signals of mate and/or rival quality because of the imposed costs through immune suppression associated with elevated testosterone levels. We demonstrate in a ¢eld experiment that male sand lizards (Lacerta agilis) exposed to elevated testosterone su¡ered from increased mass loss and tick load compared to control males. Although the ¢rst of these two results could be due to an elevated basal metabolic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 26 publications
6
138
1
1
Order By: Relevance
“…This seems to suggest a life under relatively little stress from predation compared with males (but see Olsson 1994b). In contrast, male tail regeneration is compromised by a high growth rate, perhaps because of selection for rapid growth in males that have more size-constrained reproductive success (Olsson & Shine 1996), and large males have a highly conspicuous phenotype and a reproductive success constrained by mate acquisition and mobility (Olsson et al 2000). Thus, males 'in-the-fast-lane' would be predicted to become more stressed during the mating season-and that is exactly what we see (Olsson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to suggest a life under relatively little stress from predation compared with males (but see Olsson 1994b). In contrast, male tail regeneration is compromised by a high growth rate, perhaps because of selection for rapid growth in males that have more size-constrained reproductive success (Olsson & Shine 1996), and large males have a highly conspicuous phenotype and a reproductive success constrained by mate acquisition and mobility (Olsson et al 2000). Thus, males 'in-the-fast-lane' would be predicted to become more stressed during the mating season-and that is exactly what we see (Olsson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We included the same variables for analyses in both sexes (snout-vent length (mm), tail regeneration (mm) and their interaction to look for size-dependent effects (expected particularly in males), number of observations as a proxy for exposure, number of ectoparasites as a proxy of health (Uller et al 2003) and age (years)). In males, we also included the sexlimited badge size, since this has been shown to be correlated with a number of fitness components in males (Olsson et al 2000). Predictors were backward-eliminated at p .…”
Section: Methodsmentioning
confidence: 99%
“…Ulter & Olsson (2003) showed that, under controlled laboratory conditions, prenatal exposure to high testosterone levels not only increased offspring growth rate, but also susceptibility to a common ectoparasite in the common lizard, Lacerta vivipara. Testosterone has been shown to have a negative impact on immune response in some vertebrates (Olsson et al, 2000;Peters, 2000;Casto et al, 2001;Hughes & Randolph, 2001). There are at least two potential pathways in which increased steroid levels can influence parasite load in free-ranging animals.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed husbandry, field methods and molecular protocols have been published elsewhere Olsson et al 2000) and we, therefore, only give a brief account of methods used. Males were captured by noose or by hand within a week of emergence from hibernation (ca first week in May), were blood sampled within 30 s of capturing, measured and weighed and, on the day following capture, anaesthetized and given a silastic implant (every second male received an empty control implant or one with a 4 mm crystalline testosterone column; Sigma product no.…”
Section: Methodsmentioning
confidence: 99%